The LINC00452/miR-204/CHST4 Axis Regulating Thymic Tregs Might Be Involved in the Progression of Thymoma-Associated Myasthenia Gravis - Wang, Fuqiang; Zhang, Hanlu; Qiu, Guanghao; Li, Zhiyang; Wang, Yun (Frontiers in Neurology, 2022)
Background: Myasthenia gravis (MG) is an autoimmune disease that mainly affects neuromuscular junctions and is usually associated with immune disorders in thymoma. The competitive endogenous RNA (ceRNA) hypothesis has been demonstrated to be an intrinsic mechanism regulating the development of several autoimmune diseases. However, the mechanism whereby the ceRNA network regulates immune cells in thymoma-associated myasthenia gravis (TAMG) patients has rarely been explored. Methods: RNA-seq data and clinical information of 124 thymoma patients were obtained from The Cancer Genome Atlas (TCGA) database. The patients were divided into two groups according to whether they has MG. We applied the propensity score matching (PSM) method to reduce incidence of baseline confounders. We then constructed a ceRNA network with differentially expressed RNAs between groups based on four public databases. The expression of genes of interest was validated by qPCR. Moreover, we predicted immune cells that infiltrated thymoma and then analyzed the association between immune cells and RNA in ceRNA network. To further determine the function of the mRNAs associated with immune cells in TAMG patients, we performed gene set enrichment analysis (GSEA) in thymoma patients with MG. Results: After matching, 94 patients were included in the following analysis. A total of 847 mRNAs, 409 lncRNAs and 45 miRNAs were differentially expressed between groups. The ceRNA network, including 18 lncRNAs, four miRNAs, and 13 mRNAs, was then constructed. We then confirmed that CHST4 and LINC00452, miR-204-3p and miR-204-5p were differentially expressed between TAMG and NMG patients by qPCR. Moreover, we found that the percentage of predicted regulatory T (Treg) cells was significantly decreased in TAMG patients. Further analysis indicated that the LINC00452/miR-204/CHST4 axis might regulate thymic Tregs in the progression of MG. Conclusions: In this research, we constructed a ceRNA network involved in the progression of TAMG, discovered that thymic Tregs were significantly decreased in TAMG patients, and assumed that the LINC00452/miR-204/CHST4 axis may regulate thymic Tregs in the development of TAMG. These findings may deepen our understanding of the roles of the ceRNA network in regulating TAMG and highlight the function of CHST4 in recruiting peripheral T cells in the progression of TAMG.